(untitled) (Literary Voice, 2024)
In this paper, I argue that ‘landscape’ has been used as a ‘tool’ in Indian English post-colonial children’s literature for the task of nation-building. To validate my argument, I have taken up Sonia Mehta’s Discover India series as my primary text to study the representation of the Indian landscape for children through the aesthetic of ‘picturesque;’ namely enumerative, engineered and antiquarian. It has also been argued that such a ‘picturesque’ representation of the Indian landscape helps in shaping, moulding and creating responsible, curious and knowledgeable young citizens which further accelerates the nation-building process; where the term ‘nation-building’ pertains to the post-colonial project of building the nation by creating a sense of shared identity through art, literature, science and narratives of history.